2011
DOI: 10.3928/01913913-20110118-02
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Visual Acuity Following Surgery for Correction of Head Posture in Infantile Nystagmus Syndrome

Abstract: The procedures used mainly for correction of AHP in INS do yield significant improvement in the visual acuity. This improvement is seen in patients undergoing surgery for both horizontal and vertical AHP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
6
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 32 publications
1
6
0
3
Order By: Relevance
“…4. Kopfdrehungen von im Median 35°(15-45) wurden demnach durch Rücklagerungen von medial 4-8 mm und lateral 6-12 mm stark reduziert oder komplett behoben [17]. Verglichen mit den eigenen Ergebnissen sind diese Effekte erstaunlich.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…4. Kopfdrehungen von im Median 35°(15-45) wurden demnach durch Rücklagerungen von medial 4-8 mm und lateral 6-12 mm stark reduziert oder komplett behoben [17]. Verglichen mit den eigenen Ergebnissen sind diese Effekte erstaunlich.…”
Section: Introductionunclassified
“…Systematische Studien zur Anderson-Operation (AO) erschienen um die Jahrtausendwende. Darin wurde die AO als sehr effektiv beschrieben [2,5,11,17,19,26]. In unserer Klinik lieferte die AO verglichen mit früheren Kestenbaum-Operationen (KO) nahezu identische Erfolgsraten nach 3 bis 6 Monaten [7].…”
unclassified
“…Different treatments strategies, for instance drug treatment (McLean et al, 2007) and surgery (Kumar, Shetty, Vijayalakshmi, & Hertle, 2011), have been suggested to improve the visual acuity in people with nystagmus. In order to evaluate the different strategies, eye movements before and after the treatment can be studied.…”
Section: Introductionmentioning
confidence: 99%
“…Real-world, objectively measured improvements can neither be ignored nor supplanted simply because contrived experiments claiming to accurately duplicate reality failed to do either. The statement at the end of the penultimate paragraph that treatments designed to reduce INS velocity ''rarely elicit improvements in VA'' is unsupported by two of the cited papers (Hertle et al, 3 in which there was improvement in all low-NAFX patients in whom improvement could be expected and Kumar et al, 18 which concluded, ''The procedures used mainly for correction of AHP [anomalous head posture] in INS do yield significant improvement in the visual acuity''). The third (McLean et al, 19 a clinical trial of memantine and gabapentin) failed to apply NAFX-based exclusion criteria to prevent false negatives; unfortunately, similar false negatives were also probably present in some uncited papers that showed improvements.…”
mentioning
confidence: 99%